Intensely oscillating cavitation bubble in microfluidics - Ohl, Siew-Wan (2018)
This study reports the technical breakthrough in generating intense ultrasonic cavitation in the confinement of a microfluidics channel [1], and applications that has been developed on this platform for the past few years [2,3,4,5]. Our system consists of circular disc transducers (10-20 mm in diameter), the microfluidics channels on PDMS (polydimethylsiloxane), and a driving circuitry. The cavitation bubbles are created at the gas- water interface due to strong capillary waves which are generated when the system is driven at its natural frequency (around 100 kHz) [1]. These bubbles oscillate and collapse within the channel. The bubbles are useful for sonochemistry and the generation of sonoluminescence [2]. When we add bacteria (Escherichia coli), and yeast cells (Pichia pastoris) into the microfluidics channels, the oscillating and collapsing bubbles stretch and lyse these cells [3]. Furthermore, the system is effective (DNA of the harvested intracellular content remains largely intact), and efficient (yield reaches saturation in less than 1 second). In another application, human red blood cells are added to a microchamber. Cell stretching and rapture are observed when a laser generated cavitation bubble expands and collapses next to the cell [4]. A numerical model of a liquid pocket surrounded by a membrane with surface tension which was placed next to an oscillating bubble was developed using the Boundary Element Method. The simulation results showed that the stretching of the liquid pocket occurs only when the surface tension is within a certain range.